qPCR Assays for the Detection and Quantification of Multiple Paralytic Shellfish Toxin-Producing Species of Alexandrium - Ruvindy, Rendy; Bolch, Christopher J.; MacKenzie, Lincoln; Smith, Kirsty F.; Murray, Shauna A. (Frontiers in Microbiology, 2018)
Paralytic shellfish toxin producing dinoflagellates have negatively impacted the shellfish aquaculture industry worldwide, including in Australia and New Zealand. Morphologically identical cryptic species of dinoflagellates that may differ in toxicity, in particular, species of the former Alexandrium tamarense species complex, co-occur in Australia, as they do in multiple regions in Asia and Europe. To understand the dynamics and the ecological drivers of the growth of each species in the field, accurate quantification at the species level is crucial. We have developed the first quantitative polymerase chain reaction (qPCR) primers for A. australiense, and new primers targeting A. ostenfeldii, A. catenella, and A. pacificum. We showed that our new primers for A. pacificum are more specific than previously published primer pairs. These assays can be used to quantify planktonic cells and cysts in the water column and in sediment samples with limits of detection of 2 cells/L for the A. catenella and A. australiense assays, 2 cells/L and 1 cyst/mg sediment for the A. pacificum assay, and 1 cells/L for the A. ostenfeldii assay, and efficiencies of > 90%. We utilised these assays to discriminate and quantify co-occurring A. catenella, A. pacificum and A. australiense in samples from the east coast of Tasmania, Australia.